Pengembangan Alat Edukatif Balok Iqro’ untuk Mengenalkan Huruf Hijaiyah pada Anak Usia Dini - Pitri Juwita; Irma Suryani Siregar; Sartika Dewi Harahap (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This study focuses on the development of Iqro’ block educational tools to introduce Hijaiyah letters to children at Raudhatul Athfal Al-Hilal Atar. The research aims to determine the use of Iqro’ blocks in teaching Hijaiyah letters, evaluate their effectiveness in enhancing children's recognition of these letters, and assess their practicality in the learning process. Using the Research and Development (R&D) method with the ADDIE model, this study comprises five stages: analysis, design, development, implementation, and evaluation. The results show that the Iqro’ blocks significantly improve children's ability to recognize Hijaiyah letters through interactive and enjoyable learning methods. The validation from experts indicated that the educational tool is highly feasible, achieving an average score of 4.76. Teachers also noted increased engagement and motivation among students during lessons utilizing the Iqro’ blocks. This research underscores the importance of using innovative educational tools in early childhood education to enhance the learning experience and improve literacy skills.